A árvores na Torá: uma análise simbólica e mítica - Silva, Iêda de Oliveira Caminha (2011)
The tree on the Torah: A symbolical and mythological analysis , is our desire/object, that has as objective to analyze the symbol of the tree on the books of Genesis, Exodus, Leviticus, Numbers and Deuteronomy, through Gilbert Durand's symbolic hermeneutics, that makes possible to unveil the myths decurring of the cataloged images. On the investigation, we contemplated the live tree and the human worked tree in its creative interventions. We tried, through bibliographic research, to develop the objectives: to describe, to analyze and to interpret the images of the tree and also to analyze symbolically and mythologically the influence of the symbol on the judaicchristian culture. We consider that the symbol of the tree runs through the realm of the imaginary and reveals itself as female archetype, of cosmic verticality, and, also, brings the myths as the regress to the womb, the creation, the paradise, the new rebirth, and others that in the judaic-christian culture answers to the questioning and appeases the existence.